Manajemen Nyeri Akut pada Pasien dengan Batu Ureter Level UVJ dan Batu Ginjal Dextra - Ana Khumaeroh; Lestari Sukmarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effectiveness of collaborative interventions providing analgesic therapy of the Nonsteroidal Anti-Inflammatory Drugs (NSAID) class in treating acute pain problems in patients with ureteral stones and right kidney stones. The method used is a single case study of patients with grade II & IV right hydronephrosis and right hydroureter ecausa distal ureterolithiasis UVJ level and right nephrolithiasis. The results showed that administering the NSAID class of analgesic therapy was effective as the first therapy for acute pain problems. Nurses have an important role in implementing collaborative interventions in administering analgesics, namely conducting pain assessments, assessing patient history, monitoring pain scales, observing patient responses to administering analgesics and helping patients improve comfort. In conclusion, the collaborative intervention of providing NSAID-class analgesics is effective in treating acute pain in patients with ureteral and kidney stones. Keywords: Dextra Kidney Stones, Ureteral Stones, Acute Pain, NSAID Therapy